Associations between sugar-sweetened beverages before and during pregnancy and offspring overweight/obesity in Japanese women: the TMM BirThree Cohort Study - Misato Aizawa; Keiko Murakami; Yudai Yonezawa; Ippei Takahashi; Tomomi Onuma; Aoi Noda; Fumihiko Ueno; Fumiko Matsuzaki; Mami Ishikuro; Taku Obara; Shinichi Kuriyama (Cambridge University Press, 2023)
Abstract Objective: The association between high sugar-sweetened beverages (SSB) intake during pregnancy and offspring overweight/obesity has been reported only from Western countries. The objective of this study was to examine the association between SSB intake before and during pregnancy and offspring overweight/obesity among Japanese women. Design: Japanese prospective birth cohort study. Setting: We analysed mother-offspring pairs who participated in the Tohoku Medical Megabank Project Birth and Three-Generation Cohort Study from 2013 to 2017. SSB intake during pregnancy was evaluated using the FFQ and classified into three groups: none (0 g/d), medium (<195 g/d) and high (>195 g/d). Overweight or obesity at 1 year of age in offspring was defined as having a BMI Z-score greater than 2 sd, calculated based on the BMI reference data for Japanese children. Multiple logistic regression analyses were performed to examine the associations between SSB intake before and during pregnancy and offspring overweight/obesity, after adjusting for covariates. Participants: Japanese mother-offspring pairs (n 7114). Results: The overweight/obesity rate of the offspring was 8·8 %. Pregnant women with a high intake of SSB in early to mid-pregnancy had a higher risk of overweight/obesity in their offspring compared with those who did not; the OR was 1·52 (95 % CI (1·09, 2·12)). Conclusions: High SSB intake in early to mid-pregnancy was associated with an increased risk of offspring overweight/obesity at 1 year of age.